Impact of “Three dimensional library” on the development of Information Literacy of the readers in society - Arulanantham, S.; Navaneethakrishnan, S. (National Library of Singapore, 2012)
Sri Lankan Libraries have to set their objectives to meet the needs of the society as a whole. This wills a continuous process with both formulation and implementation of new services. The political state of affairs that prevailed in our country during the last decade resulted in the loss of well reading habit among the society. “Three dimensional library” (3DL) is a new concept introduced by Foundation for Library Awareness (FOLA) in Sri Lanka. The three basic elements of the 3DL are objects and their meaning, Documents and related materials, Information bits. In the celebration of the reading month of the year 2011 October, FOLA organized an exhibition in Jaffna with the Model of a 3DL in some specific subjects. The feedbacks of this programme were collected from the viewers on random sample method, using questionnaires. The main objective of this research study is to identify and investigate the Impact of Three dimensional library on the development of Information Literacy of the readers. Using quantitative analysis of the feedback of the viewers of this programme, the findings of the study shows remarkable positive impacts. Particularly improvement in their reading habit (98%), enrichment of their information literacy level (96%), development in their educational skills (97%) and enhancement of their social responsibility (99%) were identified as major impacts of this programme. Further this suggests the need of emerge to spread and to implement this idea at national and international level to improve the information literacy of the people.